Perubahan Fungsi Homestay Sebagai Praktik Prostitusi (Studi Kasus di Tempat Wisata Desa Padusan, Kecamatan Pacet, Kabupaten Mojokerto, Jawa Timur) - Asia, Siti Nur (Universitas Islam Negeri Sunan Ampel, 2022)
The Pacet Tourism Area is well known as a tourist spot that not only offers beautiful natural scenery, but also has plenty of delicious food as well as homestays and hotels suitable for a family vacation. However, some groups take advantage of this by shifting the function of homestays into prostitution activities. The problems that the researcher wants to study are, how the process of changing the function of homestays in tourist attractions used for prostitution practices in Padusan Village, Pacet District, Mojokerto Regency, and how the Padusan community responds to prostitution activities in Padusan Village, Pacet District, Mojokerto East Java. This research uses qualitative research methods by describing community phenomena through interviews to several selected sources. This research uses Robert K. Merton's theory of deviant behavior (Anomie). That the condition of a society without norms, or a society with norms agreed upon by the whole community, but violated by some people so that it refers to the malfunction of the norm. The results of the study found that the process of changing the function of Homestay into prostitution practices in Padusan village has a driving factor, namely from internal and external so that the Padusan community is involved in it. The varied responses from the surrounding community include sympathy, anti-starch, and gray responses that have their own reasons underlying it all.